Impact of Migration on the Demographic and Religious Landscapes of Central European Countries: Legal Perspectives - Đukić, Dalibor (Migration and Central Europe: Challenges and Legal Responses, 2024)
This study examines the role of migration in transforming the demographic and religious landscapes of European countries, with a special focus on Central Europe. Since the 1950s, Europe has faced low population growth rates, which stagnated by the end of the 20th century. Migration has played a key role in reversing this trend, particularly in Central European countries such as Poland, Hungary, Slovenia, Czechia, and Slovakia, although the proportion of foreign-born residents in these countries remains below the European Union average. In 2022, member countries of the Organisation for Economic Co-operation and Development saw significant increases in asylum applications, labour migration, and international students, with family migration a leading cause of new permanent migration. Migrant populations tend to cluster in urban areas, especially in Central European capitals, except in Poland. By 2023, Europe’s population growth was bolstered by positive net migration, especially following the COVID-19 pandemic and displacement of persons from Ukraine. Despite migration’s role in population growth, its long-term effectiveness and the challenges it poses to Europe’s cultural, social, and political fabric are debated. The increasing non-working-age population strains healthcare systems and elevates old-age dependency ratios, threatening economic growth and productivity. Migration alone cannot offset the declining fertility rates; hence, pro-natalist policies are crucial. This study highlights the influence of migrants’ religiosity on Europe’s religious diversity, with implications for secularisation trends. The projected growth of religious groups, including Muslims, necessitates reassessing and reformulating legislation on religions in Europe to ensure sustainable pluralism. Ultimately, addressing Europe’s demographic challenges requires supporting the native population’s fertility rates, enhancing labour productivity, facilitating continuous education, and providing flexible employment options after retirement. These measures, while not globally altering population numbers, aim to sustain a capable environment for future sustainable population growth. Keywords: migration, demography, population ageing, workforce shortages, religion and religiosity, religious pluralism.